Analysis of Inventory Management in Oil and Gas Industry (Case Study: Joint Operating Body Pertamina-Petrochina East Java) - Bayu, Stefanus Indra; Adhiutama, Akbar (The Indonesian Journal of Business Administration, 2015)
Abstract.This research aim is to minimize high value inventory of JOB P-PEJ. The final amount of the surplus and dead stock inventory is US $ 2,017,053.19 in November 2014. The causes of this high number is lack of discipline to input data, lack of inventory management control, and lack of coordination between user, stock analyst, warehouse staff and supplier. By eliminating any root cause, expected the inventory valueexpected to be reduced as low as possible. Training of motivation and training knowledge of Work Procedures Guidelines 007 is a solution to overcome the lack of discipline. For lack of inventory management control, the solution is divide the materials with ABC Classification. After divided, the next stage is determine ROP, ROQ, SS continuously. And the solution for lack of coordination between every parties in supply chain, implementing Third Party Logistics (3PL) is the answer. The result of the research indicates that inventory value is decrease after implementing all of the solutions.Keywords: Inventory Management, Oil and Gas Industry, Joint Operating Body, Pertamina, Petrochina